Penerapan keterampilan tingkat tinggi (HOTS) dan penguatan pendidikan karakter (PPK) dalam penulisan soal bagi guru SD - Sulis Setyawati; Bambang Sumadyo; Adi Permana (Presisi Jurnal Pengabdian Masyarakat, 2022)
Instructional Oriented Higher Order Thinking Skills (HOTS) is one of the efforts that can be made to improve the quality of learning and graduates. This was implemented as a follow-up to Indonesia's low ranking in the Program for International Student Assessment (PISA) compared to other countries. Higher order thinking skills must be accompanied by Strengthening Character Education (PPK). Character education is an educational system that aims to instill certain character values ​​to students in which there are components of knowledge, awareness or willingness, as well as actions to carry out these values. Character education is closely related to moral education where the goal is to shape and train individual abilities continuously for self-improvement towards a better life. Keywords : Higher Order Thinking Skills, Character Education